Pengembangan Modul Mata Kuliah Media dan Bahan Ajar Bahasa Indonesia Berbasis Literasi Kritis di Universitas PGRI Silampari - Sri Murti; Rusmana Dewi; Ayu Sugiarti; Vella Sabrila Aisyah (Journal of Elementary School (JOES), 2023)
This study aims to determine the development of modules, valid, practical and efficient for Critical Literacy-based Indonesian Media and Teaching Materials courses at PGRI Silampari University. This study uses the R&D (research and development) development model as a guideline for developing critical literacy-based modules for Media Courses and Indonesian Teaching Materials. The sample in this study were VA semester students of the Indonesian Language and Literature Education Study Program at PGRI Silampari University for the 2022/2023 academic year. Data collection techniques carried out included interviews, questionnaires and tests. There are analysis techniques in the form of interview data analysis, questionnaire data analysis and test data analysis. Furthermore, the Indonesian Language Media and Teaching Materials module is valid in the "very good" category with a result of 0.812. From the results of the one to one prototype test, small group test and large group test it is concluded that the Indonesian Language Media and Teaching Material module is practical to use. Data from formative test results show that the average student score is 81.14 in the very good category so it is concluded that the Indonesian Language Media and Teaching Materials module is effectively used in lectures. Keywords: Development, Modules, Indonesian Language.